Stigmatizing attitudes toward mental illness among caregivers of patients with mental disorders in China - Hao, Yuzhu; Wu, Qiuxia; Wang, Xuyi; Ma, Yuejiao; Wang, Yunfei; Peng, Pu; Wang, Xin; Yang, Qian; Liu, Yueheng; Li, Manyun; He, Li; Wang, Qianjin; et al. (Frontiers in Public Health, 2023)
Objective: This study aimed to investigate stigmatizing attitudes towards depression, schizophrenia, and general anxiety disorder (GAD) among caregivers of patients with mental disorders in China. Methods: A cross-sectional study was conducted among 607 caregivers in China, using vignettes that described three mental illnesses. The caregivers’ attitudes, other people’s towards individuals with mental disorders, and the willingness to come into contact with them were collected. Results: In three vignettes, caregivers agreed that positive outcomes outnumbered negative ones. The top two endorsements of stigma were “the person could snap out of the problem” and “people with this problem are dangerous”. In perceived stigma, caregivers in GAD vignette agreed more that most other people believed this problem is not a real medical illness compared to schizophrenia. The rates of endorsement of unpredictability were significantly different among schizophrenia (57.2%) and depression (45.5%) vignette, GAD (45.6%), and schizophrenia vignette. In personal stigma, the caregivers tended to avoid people in depression vignette than in GAD. The caregivers were most unwilling to let the person marry into their family, especially in the schizophrenia vignette. Conclusion: Despite the stigma and desire for social distance associated with schizophrenia, depression, and GAD, caregivers often expect positive outcomes. Actions should be taken to improve caregivers’ knowledge about mental health and reduce the stigma.